Denitrosation of Aryl- N -nitrosamines by a Transnitrosation Strategy Using Ethanethiol and p -Toluenesulfonic Acid under Mild Reaction Conditions - Kanaujiya V.K.; Tiwari V.; Baranwal S.; Srivastava V.; Kandasamy J. (My University, 2025)
A convenient and practical route is reported for the denitrosation of aryl-N-nitrosamines under mild reaction conditions using ethanethiol and PTSA. The reactions proceeds at room temperature and the amines are obtained in good to excellent yields. Many functional groups that are susceptible to reduction were stable during the denitrosation. A broad substrate scope and easy operations are salient features of this method. © 2022 Georg Thieme Verlag. All rights reserved.